Effects of covid-19 pandemic on physical activity and sedentary behaviour among Malaysia undergraduate university students - Yasrani, Ahmad Yasri Ahmad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Limited studies have been conducted in Malaysia to examine the effect of the COVID-19 pandemic directly on the undergraduate university population of Malaysia. Therefore, this study aimed to investigate the changes of physical activity, sedentary behaviour, and body weight among Malaysia undergraduate university students before, during and after Movement Control Order (MCO) 1.0. This cross-sectional study involved 136 Malaysian undergraduate students. The Godin Leisure-Time Exercise Questionnaire (G-LTEQ) was used to assess the physical activity and the International Physical Activity Questionnaire-Short Form (IPAQ-SF) was used to assess sedentary behaviour of the respondents. Body weight before, during and after the MCO 1.0 was self-reported by the respondents. Tertile splits were performed on the pre-MCO 1.0 total physical activity score and the following groups were established: low, moderate, and high pre-MCO 1.0 physical activity group. Separated the three pre-MCO 1.0 physical activity group (low, moderate, high) by time ANOVAs were conducted for total physical activity, sedentary behaviour, and bodyweight. The results revealed that there was a significant difference in physical activity and body weight but there was no significant difference in sedentary behaviour. Based on the findings obtained, it can be concluded that this COVID-19 pandemic brings negative effect on physical activity, sedentary behaviour, and bodyweight.